FROM CLASSROOM TO STAGE: ARABIC DRAMA CONTEST AS AN EXPERIENTIAL APPROACH IN ARABIC CURRICULUM DEVELOPMENT PONDOK MODERN DARUSSALAM GONTOR PUTRI 1ST CAMPUS - Fairuz Subakir; Agus Yasin; Ahmad Ario Sofian; Nur Fera Khalifah; Nuraeni Rahmawati (Irfani, 2024)
This study examines the role of the Arabic Drama Contest Antar Rayon as an experiential approach in Arabic curriculum development at Pondok Modern Darussalam Gontor Putri Campus 1. Using a qualitative educational ethnography approach, this research explores how drama-based activities contribute to communicative competence, hidden curriculum, and curriculum implementation within the pesantren educational environment. Data were collected through participant observation, in-depth interviews, and documentation involving Arabic teachers, drama supervisors, student organizers, and student participants. The findings reveal that the Arabic Drama Contest functions as an authentic communicative learning environment that strengthens students’ speaking fluency, confidence, vocabulary mastery, creativity, and collaborative interaction. The activity also serves as a hidden curriculum transmitting values of discipline, leadership, responsibility, and teamwork through participatory educational practices. Furthermore, the study demonstrates that curriculum development in pesantren extends beyond formal classroom instruction into cultural performances and student organizational activities integrated within the bi’ah lughawiyyah. The study concludes that drama-based experiential learning provides an innovative and holistic model for Arabic curriculum development in Islamic boarding schools by integrating linguistic competence, character formation, and cultural participation into a unified educational ecosystem.